The Diagnostic Yield of Chromosomal Microarray Analysis in Third-Trimester Fetal Abnormalities - Elron, Eyal; Maya, Idit; Shefer-Averbuch, Noa; Kahana, Sarit; Matar, Reut; Klein, Kochav; Agmon-Fishman, Ifat; Gurevitch, Merav; Basel-Salmon, Lina; Levy, Michal (American Journal of Perinatology, 2024)
Objective This study aimed to determine the diagnostic yield of chromosomal microarray analysis (CMA) performed in cases of fetal abnormalities detected during the third trimester of pregnancy.Study Design A retrospective review of medical records was conducted for women who underwent amniocentesis at or beyond 28 weeks of gestation between January 2017 and February 2023. CMA results of pregnancies with abnormal sonographic findings not detected before 28 weeks were included.Results A total of 482 fetuses met the inclusion criteria. The average maternal age was 31.3 years, and the average gestational age at amniocentesis was 32.3 weeks. The overall diagnostic yield of CMA was 6.2% (30 clinically significant copy number variations [CNVs]). The yield was 16.4% in cases with two or more fetal malformations, while cases with a single anomaly revealed a diagnostic yield of 7.3%. Cases presenting isolated polyhydramnios or isolated fetal growth restriction had a lower yield of 9.3 and 5.4%, respectively. Of the 30 clinically significant cases, 19 (or 63.4%) exhibited recurrent CNVs. The remaining 11 cases (or 36.6%) presented unique CNVs. The theoretical yield of Noninvasive Prenatal Testing (NIPT) in our cohort is 2% for aneuploidy, which implies that it could potentially miss up to 70% of the significant findings that could be identified by CMA. In 80% of the fetuses (or 24 out of 30) with clinically significant CNVs, the structural abnormalities detected on fetal ultrasound examinations corresponded with the CMA results.Conclusion The 6.2% detection rate of significant CNVs in late-onset fetal anomalies confirms the value of CMA in third-trimester amniocentesis. The findings underscore the necessity of CMA for detecting CNVs potentially overlooked by NIPT and emphasize the importance of thorough genetic counseling.Key Points
Keywords: chromosomal microarray analysis; third trimester; ultrasound; sonographic anomalies; noninvasive prenatal testing; amniocentesis; late-onset fetal anomalies